2014
DOI: 10.5535/arm.2014.38.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recovery of Functional Swallow After Gastrostomy Tube Placement for Dysphagia in Stroke Patients After Inpatient Rehabilitation: A Pilot Study

Abstract: ObjectiveTo determine predictors of early recovery of functional swallow in patients who had gastrostomy (percutaneous endoscopic gastrostomy [PEG]) placement for dysphagia and were discharged to inpatient rehabilitation (IPR) after stroke.MethodsA retrospective study of prospectively identified patients with acute ischemic and hemorrhagic stroke from July 2008 to August 2012 was conducted. Patients who had PEG during stroke admission and were discharged to IPR, were studied. We compared demographics, stroke c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
2
25
1
Order By: Relevance
“…Positive predictors of recovery of functional swallowing after a stroke are hemorrhagic stroke, younger age, and left-sided stroke. 146 Even during the first 6 months, improvement of swallowing is likely. It is therefore important to repeat assessment of the swallowing function at regular intervals.…”
Section: Dysphagia In Special Situationsmentioning
confidence: 99%
“…Positive predictors of recovery of functional swallowing after a stroke are hemorrhagic stroke, younger age, and left-sided stroke. 146 Even during the first 6 months, improvement of swallowing is likely. It is therefore important to repeat assessment of the swallowing function at regular intervals.…”
Section: Dysphagia In Special Situationsmentioning
confidence: 99%
“…20 Crisan et al found that age and side of stroke were significant predictors of swallowing recovery. 21 Despite these previous studies, the prediction of swallowing outcomes remains a difficult task. Recently, Gandolfo et al created a PreDyScore ((modified Rankin Scale, assessing degree of dependence (mRS) + 1/BMI) × 100) to indicate gastrostomy tube placement, 22 and Galovic et al developed and validated a prognostic model for swallowing recovery and enteral tube feeding after ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A functional magnetic resonance imaging and diffusion‐weighted imaging study supported a role for increased contralesional somatosensory resources and ipsilesional anterior cerebellum feed‐forward loops for dysphagia recovery 20 . Crisan et al found that age and side of stroke were significant predictors of swallowing recovery 21 . Despite these previous studies, the prediction of swallowing outcomes remains a difficult task.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this is that although contraindications for oral intake and indication criteria for enteral and parenteral nutrition have been formulated, 8 there are no clear indicators for the resumption of oral intake. Although attempts to assess swallowing function and wean patients from feeding tubes following enteral or parenteral nutrition have been reported, 9,10 these have mostly focused on acute 11 or convalescent 12,13 inpatients, and few studies have addressed patients living at home.…”
Section: Introductionmentioning
confidence: 99%